Development of a goalkeeper for the Middle Size League - Castro, Rafael Filipe dos Reis (2015)
CAMBADA (Cooperative Autonomous Mobile Robots with Advanced Distributed Architecture) is the robotic soccer team of the University of Aveiro that participates in RoboCup Middle Size League. This team was created by researchers from research units IEETA and ATRI. Robotics is an area in constant evolution but the work developed within this thesis will hardly be overcome even with the constant progress in this area, since the primary goal of the goalkeeper will always remain the same: not conceding goals. Contributions presented in this dissertation are in terms of high-level behavior of the goalkeeper of the team CAMBADA , however not everything applies exclusively to the goalkeeper, it is important for any eld player and can be applicable in the near future. This work addressed two main topics, the rst one is the positioning of the goalkeeper on the eld that extends to the run-game placements, near the goal posts placement and a more aggressive defense behavior with pressure to the player with the ball. The second topic addressed is the ability of detection and defend shots by air. The con guration of the goalkeeper in a simple way has been one of the objectives of this study, to avoid at all costs that his actions are too static and can easily take advantage of this easy setup to change the goalkeeper behavior depending on the opponents of CAMBADA. A graphical user interface to control these settings was developed. The work has been tested in the laboratory di ering greatly from the previous behavior that was very defensive and whose radius of action was very close to the goal line for a more unpredictable, closer to an human Goalkeeper behavior that applying pressure to the opponent attacker feature a wider range of defensive options.